(untitled) (Semiárida, 2020)
The objective of these experiments was to study the different cereal grains ("tricepiro and trilicale") as energy sourees in growing-finishing diets. The hybrid gilts (Yorl<shire x Landrace x Duroc Jersey) were fed sd-/lbltum during 56 days with: 16% C.P.; 3.300 Kcal DElkg, 1,30% Ca; 0,93% P and 0,82% of Iys (Dry weight). The first experiment was done wilh tricepiro "Don René" (T1), triticale "Tehuelche" (T2) and the mixture of both triticale (50-50) "Don Erman and Don Frank" (T3), being compare with Com (T0)as a control in hybrid gilts between 57 - 100 kg Iiveweight, confined in individual boxes. In a second trial triticale "Yagén" (T4) and triticale "Don Santiago" (T5) were evaluated versus Corn (T0). AII other experimental conditions being the same as for trial one. The results of the first trial were: Oally welght galn (p<0,025): T2= 868,62 9 a; T3= 840,35 sb; T0=753,50 bc and T1= 729,25 c. Feed Intake In sil the period (p<0,01):T0= 181,95 kg a; T3= 167,85 b, T2= 164,90 be and T1= 155 c. Conversion efflciency (p<0,01): T0=4,31:1 8; T1= 3,83:1 b; T3= 3,59:1 bc and T2= 3,40:1 c. Backfat thlckness (p<0,01):T0- 26,12 mm a; T3= 23,19 b; T1= 20,82 C and T2= 19,91 c. Fatty acid ratio: T2= 1,17% of oleic acid, T3= 1,59; T0=3,65 and T1= 3,67. Second trial results were: Oally welght gain (p<00,01):T0= 948 9 a; T5= 942 a; and T4= 883 b. Feed Intake In all th8 period (p<0,01): T4= 159,55 kg a; T5= 173,34 b, and T0= 169,51 b, but not found statistical difference In conversion efflciency and backfat thickness. Fatty acid ratio: T2= 1,17% of oleic acid, T3= 1,59; T0=3,65 and T1= 3,67. We conclude that trilicale Tehuelche, the mixture of Don Erman and Don Frank, and Don Santiago can be included in growing-finishing diets for hybrid gilts on account of the daily weight gain and faed conversion results obtained. tricepiro Don René showed the best result for backfat thickness and feed intake. indeed, Triticales tried in these diets produced carcasses with excellent values of backfat thickness.